Letter to Jane Tolmach from Ginger Gherardi - Ginger Gherardi::::::
In this July 15, 1975 letter, Simi Valley Councilwoman Ginger Gherardi describes the formation and activities of the California Elected Women's Association for Education and Research (CEWAER), which promotes communication, shared problem-solving, and greater political impact among elected women statewide. She notes recent conferences featuring prominent speakers and workshops, and emphasizes the value of ongoing collaboration among Ventura County's elected women. Gherardi invites recipients to attend the first Ventura County meeting on August 9, 1975, at Jane Tolmach's home in Oxnard.